2005
DOI: 10.1159/000091375
|View full text |Cite
|
Sign up to set email alerts
|

Mice Deficient in Biglycan and Fibromodulin as a Model for Temporomandibular Joint Osteoarthritis

Abstract: The temporomandibular joint (TMJ) within the craniofacial complex is unique. In humans, the TMJ can become diseased resulting in severe and disabling pain. There are no cures for TMJ disease at this time. Animal models of TMJ disease are scarce, but some exist, and they are described in this paper. We present in greater detail one animal model that is deficient in two extracellular matrix (ECM) proteoglycans, biglycan (BGN) and fibromodulin (FMOD). Doubly deficient BGN/FMOD mice develop premature TMJ osteoarth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 67 publications
0
39
1
Order By: Relevance
“…4). At 4 and 8 weeks, experimental condyles displayed classical histopathological features of osteoarthritis (3,21,22), including surface irregularities and fissures (black triangles), a multifocal decrease in cells (asterisks), and the formation of chondrocyte clusters (black arrows) (Fig. 4a, top and middle panels).…”
Section: Resultsmentioning
confidence: 99%
“…4). At 4 and 8 weeks, experimental condyles displayed classical histopathological features of osteoarthritis (3,21,22), including surface irregularities and fissures (black triangles), a multifocal decrease in cells (asterisks), and the formation of chondrocyte clusters (black arrows) (Fig. 4a, top and middle panels).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, data from a number of recent studies indicated that deletions of type VI and IX collagens, matrilin 3, biglycan, and fibromodulin-all of which are components of the pericellular matrix-result in early onset articular cartilage degeneration. [22][23][24] Although it is clear that the disruption of the pericellular matrix is implicated in the initiation of articular cartilage degeneration, the question remains as to how the pericellular matrix is degraded and then leads to progression characterized by loss of aggrecan and collagen in the interterritorial matrix.…”
Section: Discussionmentioning
confidence: 99%
“…However, a biological explanation for the propensity of females in the TMD population has not been identified. Because mouse models for both FSHD and TMD have been developed or are underway (28,29), the ability to measure the normal and pathological functional state of masticatory muscles could be utilized to assess potential therapies for these disorders.…”
Section: Discussionmentioning
confidence: 99%